2014
DOI: 10.1149/2.093403jes
|View full text |Cite
|
Sign up to set email alerts
|

Role of 1,2,4-Triazole as a Passivating Agent for Cobalt during Post-Chemical Mechanical Planarization Cleaning

Abstract: Cobalt (Co) has been considered as one of the candidates for the barrier material in copper (Cu) interconnects. As a metal that is less noble than copper, Co poses two challenges to the integration scheme. For example, during the post-chemical mechanical planarization (CMP) cleaning step, corrosion of Co and galvanic corrosion between Co and Cu may occur. To minimize such corrosion, a corrosion inhibitor is often added into the post-CMP cleaning solution. The present study investigates the interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…Zhong et al 30 showed that 5 mM 1,2-4 Triazole (TAZ) and 3 mM citric acid containing aqueous solution prevented the galvanic corrosion of Cu-Co couple for post-CMP applications. Alety et al 31 found that an aqueous solution consisting of glycine and TAZ to be most effective among the many solutions they tested for cleaning ultrathin ∼2 nm Co films and controlling the galvanic corrosion between the Cu-Co couple.…”
Section: Choice Of Inhibitormentioning
confidence: 99%
“…Zhong et al 30 showed that 5 mM 1,2-4 Triazole (TAZ) and 3 mM citric acid containing aqueous solution prevented the galvanic corrosion of Cu-Co couple for post-CMP applications. Alety et al 31 found that an aqueous solution consisting of glycine and TAZ to be most effective among the many solutions they tested for cleaning ultrathin ∼2 nm Co films and controlling the galvanic corrosion between the Cu-Co couple.…”
Section: Choice Of Inhibitormentioning
confidence: 99%
“…Several authors [18][19][20][21][22][23][24][25][26] have investigated cobalt polishing for such applications where RR requirements are typically <20 nm/min and Co loss due to corrosion has to be as close to zero as possible, since even a minute loss of Co material can degrade the device reliability significantly. Hence, since the potential gap between Co and Cu is a large ∼0.61 V, it is very important to lower this to ∼10-20 mV.…”
mentioning
confidence: 99%
“…Using polishing and cleaning formulations at alkaline pH values galvanic corrosion can be highly suppressed. 12,13 However, under CMP conditions, due to abrasion of passive oxide layers galvanic corrosion may continue to occur but the repassivation kinetics of the corroding surface would determine if corrosion is likely to continue after the cessation of polishing.…”
Section: Galvanic Corrosion Issuesmentioning
confidence: 99%